The nucleopolyhedroviruses of Rachiplusia ou and Anagrapha falcifera are isolates of the same virus - Harrison, Robert L.; Bonning, Bryony C. (Journal of General Virology, 1999)
The 7·8 kb EcoRI-G fragment of Rachiplusia ou multicapsid nucleopolyhedrovirus (RoMNPV), containing the polyhedrin gene, was cloned and sequenced. The sequence of the fragment was 92·3% identical to the sequence of the corresponding region in the Autographa californica (Ac)MNPV genome. A comparison of the EcoRI-G sequence with other MNPV sequences revealed that RoMNPV was most closely related to AcMNPV. However, the predicted amino acid sequence of RoMNPV polyhedrin shared more sequence identity with the polyhedrin of Orygia pseudotsugata MNPV. In addition, the RoMNPV sequence was almost completely identical (99·9%) to a previously published 6·3 kb sequence of Anagrapha falcifera MNPV (AfMNPV). The Eco RI and HindIII restriction fragment profiles of RoMNPV and AfMNPV also were nearly identical, with an additional EcoRI band detected in RoMNPV DNA. Bioassays of these viruses with three different hosts (the European corn borer, Ostrinia nubilalis H übner, the corn earworm, Helicoverpa zea Boddie, and the tobacco budworm, Heliothis virescens Fabricius) failed to detect any differences in the biological activities of RoMNPV and AfMNPV. These results indicate that RoMNPV and AfMNPV are different isolates of the same virus. The taxonomic relationship of Ro/AfMNPV and AcMNPV is discussed.